The Open Access Initiative in Access to Technical and Scientific Information in Health Sciences - DOI: 10.3395/reciis.v1i1.50en - Javier Sanz Valero; Jorge Veiga de Cabo; Luis D. Castiel (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2007)
The Open Access Initiative (OAI) relates to documents published electronically, and allows free and unrestricted access to the full text of scientific and research literature via the Internet. This assumes the free use of scientific information, as long as its authorship is recognized. The three main statements about the OAI are contained in the declarations of Budapest (2002), Bethesda (2003) and Berlin (2003). Open access is compatible with copyright, copyleft, peer review, printing, preservation and other characteristics associated with conventional academic literature. The most relevant difference consists in the fact that readers are not charged for access to the information, and therefore there are no barriers to research. Even so, the success of the OAI does not depend only on the availability of documents, but also on the support of the scientific community.